Machine Learning: An Effective Technique for Health Data Classification - Behar, Nishant; Shrivastava, Manish (International Journal of Computer Sciences and Engineering, 2025)
Health is precious for every life. But there are many diseases which fall under the category of dangerous or critical due to it mortality rate. Such diseases can be cured or at least prevented if they are identified in their earlier stages. For the proper diagnosis of these diseases, data mining techniques using machine learning methods- k-NN, Naïve Base, Decision trees, Support Vector Machine plays very significant role. In this paper the focus was on finding techniques applied for the common disease classifications, the accuracy of methods reported, dataset used and pros and cons of these methods and concluded with the open challenges and opportunities for further research in health care sector